Beyond Unicorns : Harnessing Digital Technologies for Inclusion in Indonesia - World Bank (Washington, DC: World Bank, 2021)
Similar to many other countries around the world, the COVID-19 (coronavirus) pandemic has hit Indonesia hard. Latest estimates suggest that about 5.1 million people—equivalent to 2.4 percent of the working-age population—have lost their jobs, while an additional 24 million have had to work reduced hours due to the pandemic. As many as 50 percent of workers have experienced a reduction in earnings. The impact on living standards has been devastating, with more than 2.2 million Indonesians estimated to have been pushed into COVID-19-induced poverty in 2020. One unexpected silver lining from the crisis, however, has been the turbo-charged adoption of digital technologies. Businesses, both large and small, have flocked to digital technologies to try to ensure the continuity of their operations. School closures have forced students and teachers to adapt and explore digitally enabled remote learning options, including the adoption of a variety of EdTech solutions. HealthTech apps enabling remote consultations and the delivery of medicine have seen unprecedented growth in adoption rates. Confined at home due to mobility restrictions, Indonesians have switched to the internet for their entertainment and social needs, driving sharp growth in the usage of digital media (music and video streaming) and communications applications. With this pandemic-induced flight to digital expected to be permanent to a large extent, there is excitement about an even greater acceleration in what was already the fastest growing digital economy in Southeast Asia. But at the same time questions have also emerged about the possibility of the differential access to and adoption of digital technologies compounding existing inequalities. For a country that considers achieving balanced development one of its key priorities, this is an important new challenge.